Hubungan peran guru bimbingan dan konseling dengan motivasi belajar siswa sekolah menengah kejuruan - Heru Sriyono; Suparmin Suparmin (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2017)
This study aims to investigated correlation between guidance and counseling teacher role with student learning motivation. Research method that used were quantitative with survey approach. Data and data resources in this research from students of XI SMK Muhammadiyah 9 Jakarta amounting 254 students. Sample in this research amount 35 students from students of XI Administrasi Perkantoran with purposive sampling technque. Instrument in this research is questionnaire. Data were analyzed by product moment correlation. The result of this research show that guidance and counseling teacher role with student learning motivation is was low. It is known through the analysis and processing of questionnaire data obtained correlation coefficient into the low category that is equal to 0.260.